2016
DOI: 10.3892/or.2016.5136
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Treg cells and tumor-associated macrophages in the tumor microenvironment of epithelial ovarian cancer

Abstract: Abstract. Epithelial ovarian cancer (EOC) is the most lethal gynecological malignancy. Inflammatory cells in the EOC microenvironment play a key role in tumor progression. In the present study, we investigated the mechanism of the accumulation of regulatory T cells (Tregs) induced by interleukin-10 (IL-10) derived from tumor-associated macrophages (TAMs) in the EOC microenvironment. The frequency of Tregs and TAMs was detected by immunofluorescence in 40 EOC tissues and 20 benign ovarian tumors, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 28 publications
1
44
0
1
Order By: Relevance
“…Treg cells are not only responsible for the evasion of cancer cells from immune surveillance, but also cooperate with other immune cells, including TAMs, which are predominantly from M2 subgroups [29,30]. These subgroups are responsible for the secretion of TGF-beta and Il-10 that support the differentiation of Treg cells [31]. TAM may also interact with Treg cells in the tumor microenvironment, producing exosomes, such as miRNAs [4].…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells are not only responsible for the evasion of cancer cells from immune surveillance, but also cooperate with other immune cells, including TAMs, which are predominantly from M2 subgroups [29,30]. These subgroups are responsible for the secretion of TGF-beta and Il-10 that support the differentiation of Treg cells [31]. TAM may also interact with Treg cells in the tumor microenvironment, producing exosomes, such as miRNAs [4].…”
Section: Discussionmentioning
confidence: 99%
“…High frequency of Tregs in OvCa specimens was associated with significantly shorter overall survival time. Mechanistic studies showed that IL‐10 secreted by TAMs increases the frequency of Tregs through activation of Foxp3 during T‐cell differentiation . Consistently, Treg percentages were significantly higher in patients with OvCa than with benign ovarian tumors (BOT) or healthy controls.…”
Section: Introductionmentioning
confidence: 77%
“…Mechanistic studies showed that IL-10 secreted by TAMs increases the frequency of Tregs through activation of Foxp3 during T-cell differentiation. 82 Consistently, Treg percentages were significantly higher in patients with OvCa than with benign ovarian tumors (BOT) or healthy controls. Higher percentages of Tregs were found in patients with stage III/IV than stage I/ II OvCa.…”
Section: Tumor-associated Lymphocytes (Tils) Comprise T-cells and Rementioning
confidence: 83%
See 2 more Smart Citations